Association of Reduced Lung Function With Major Depressive Disorder - Afreen, Khandaker Nadia; Imtiaz, Masud; Rouf, Mahadi Abdur; Mollika, Rono; Nahar, Lutfun; Gomes, Richmond Ronald (Bangladesh Critical Care Journal, 2017)
Background: Major Depressive Disorder (MDD) is associated with reduced lung function. Objectives: To observe & compare FEF25%-75% in Major Depressive Disorder patients with control group. Methods: This prospective study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from January to December, 2014 to assess the lung function status in newly diagnosed MDD patients. For this, 30 newly diagnosed female MDD patients (group B), aged 20 to 50 years were enrolled from the Department of Psychiatry of BSMMU. For control (group A) age, BMI, and occupation matched 30 apparently healthy females were randomly selected by personal contact. FEF25%-75% of all subjects were assessed by a portable digital spirometer (PONY FX, Cosmed, Italy). For statistical analysis, ANOVA, Independent samplet test were done and p value ?0.05 was considered as level of significance. Results: FEF25%-75%was significantly lower (p?0.001) in all MDD patients than control. Conclusion: From this study it may be concluded that the ventilatory lung function is significantly reduced in newly diagnosed MDD patients. Bangladesh Crit Care J September 2017; 5(2): 126-128